Strategic Management of Digitalization in PPTQ (Pondok Pesantren Tahfidz Al-Qur’an) to Enhance the Effectiveness and Quality of Al-Qur’an Learning - Sya'roni Sya'roni (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Digitalization of Islamic education often prioritizes technical efficiency over spiritual authenticity, creating a tension between technological demands and the preservation of talaqqi and sanad traditions in Qur'anic learning. This article examines the strategic management of digitalization within the Qur'anic Recitation Development Program (PPTQ) at Ma'had al-Jami'ah, UIN Siber Syekh Nurjati Cirebon. A qualitative case study was conducted involving 25 participants (program leaders, managers, five tutors, and fifteen students) through semi-structured interviews, passive observation, and document analysis. Data were analyzed using Miles, Huberman, and Saldaña's framework with Mintzberg's Five-P Strategy. Six main findings emerged: digitalization improves administrative efficiency and learning flexibility; data-driven management enhances program effectiveness; students' recitation quality increases significantly; talaqqi and sanad remain irreplaceable; digitalization is perceived as a means (wasilah) not an end (ghayah); and spiritual concentration declines during online sessions. The study contributes a novel Hybrid Sanad-Based Digital Management model that integrates Mintzberg's Five-P Strategy with Qur'anic values through a three-layer hierarchical structure (Qur'anic values as strategic foundation, talaqqi as core pedagogical authority, and digital as supporting infrastructure). This model demonstrates that technology can strengthen, rather than weaken, traditional Qur'anic pedagogy when properly bounded by epistemological and affective-spiritual limits. These findings challenge the dominant dichotomous assumption that technology and tradition must be opposed, offering an integrative framework for Qur'anic learning digitalization that preserves sanad and adab in the digital era